Tim3 and PD-1 as a therapeutic and prognostic targets in colorectal cancer: Relationship with sidedness, clinicopathological parameters, and survival - Mokhtari, Zahra; Rezaei, Marzieh; Sanei, Mohammad Hossein; Dehghanian, Amirreza; Faghih, Zahra; Heidari, Zahra; Tavana, Shirin (Frontiers in Oncology, 2023)
Background Colorectal cancer (CRC) is a heterogeneous disease that complicates predicting patients’ prognosis and their response to treatment. CRC prognosis is influenced by the tumor microenvironment (TME). The immune system is a critical component of the TME. Programmed cell death receptor 1 (PD-1) and T-cell immunoglobulin and mucin-domain containing-3 (Tim3) are inhibitory immune checkpoints that regulate immune response and may provide prognostic power. However, the effect of their expressions and co-expressions on the CRC prognosis remains unclear. Accordingly, this study aimed to investigate the prognostic value of the CD8, CD3, PD-1, Tim3 expression, and PD-1/Tim3 co-expression in patients with CRC. Materials and Methods One hundred and thirty six patients with CRC who underwent curative surgery were enrolled in the study. Immunohistochemical staining was performed for PD-1, Tim3, CD8, and CD3, and the expression of each marker was evaluated in the center of the tumor (CT), invasive margin (IM), and adjacent normal-like tissue. Result Our results indicated that high expression of PD-1 in IM was significantly associated with lower TNM stage, T-stage, M-stage, lack of metastasis, the presence of tertiary lymphoid structure (TLS), lack of recurrence (in the left-sided tumors), and larger tumor size (in right-sided tumors) (P<0.05). High expression of PD-1 in IM was also associated with improved overall survival (OS) in a subgroup of patients with high CD8 expression. High Tim3 expression in CT was associated with higher M-stage (M1) (in left-sided CRCs) (P<0.05). It was also associated with decreased OS in total cohort and left-sided CRCs and represented an independent prognostic factor for CRC patients in multivariate analysis. PD-1 and Tim3 co-expression had no synergistic effects on predicting OS. Conclusion Our findings suggest that the clinicopathological and prognostic significance of immune system-related markers such as CD8, PD-1, and Tim3 depends on the primary tumor sides. We also showed that Tim3 could act as a prognostic factor and therapeutic target in CRC. This marker is probably a more preferred target for immunotherapy than PD-1, especially in left-sided CRCs.